Continuous casting submersed nozzle slag line and submersed nozzle

By using stable zirconia, monoclinic zirconia and nanocarbon black materials in the immersed water outlet slag line, combined with improved inner pore material, the problem of insufficient anti-protective slag line of immersed water outlet slag line is solved, and the resistance is improved Thermal shock and corrosion resistance reduce manufacturing costs and enhance the safety of immersion ports and casting quality.

CN119176721APending Publication Date: 2024-12-24BAOSHAN IRON & STEEL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310739943.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-06-21
Publication Date
2024-12-24

AI Technical Summary

Technical Problem

The existing continuous casting immersion water outlet slag line has insufficient protection slag corrosion resistance under the conditions of high continuous casting furnaces, resulting in an increased risk of slag line perforation, high manufacturing cost and affecting the quality of molten steel.

Method used

Using a combination of stable zirconia and monoclinic zirconia, nanocarbon black and flake graphite are added to reduce the carbon content to improve the thermal shock and corrosion resistance of the slag line, and improve the inner pore material to enhance the overall corrosion resistance.

Benefits of technology

It significantly improves the corrosion resistance and thermal shock resistance of the slag line, extends the service life, reduces manufacturing costs, and enhances the safety of immersion water outlets and casting quality.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004296981110000061
    Figure BDA0004296981110000061
  • Figure BDA0004296981110000071
    Figure BDA0004296981110000071
Patent Text Reader

Abstract

The slag line material comprises the following components in percentage by weight: more than or equal to 85% of stable zirconium oxide and monoclinic zirconium oxide, 0.5-3.0% of nano carbon black, 3-9% of crystalline flake graphite and 2-7% of phenolic resin, and the monoclinic zirconium oxide is more than 0 and less than or equal to 5%. On the premise of ensuring that the submerged nozzle slag line has high thermal shock resistance, the erosion resistance of the slag line is further improved, the number of continuous casting furnaces is increased, the cost of a continuous casting procedure is reduced, the quality of a casting blank is improved, the erosion resistance of the inner hole body is improved by improving the material of the inner hole body, and the service life of the inner hole body is prolonged. Slag line perforation possibly caused when the number of casting furnaces is high is avoided, and therefore the use safety of the submersed nozzle is greatly improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of steelmaking, and in particular relates to a continuous casting submerged nozzle slag line and a submerged nozzle. Background Art

[0002] The submerged nozzle is a refractory sleeve installed at the bottom of the tundish in the continuous steel casting equipment and inserted below the molten steel level in the crystallizer. It plays a very important role in continuous casting production. The submerged nozzle is installed below the tundish, and the molten steel passes through the inside of the submerged nozzle, and the part below the slag line is immersed in the molten steel in the crystallizer. The role of the submerged nozzle in the continuous casting process mainly includes three aspects: one is to prevent the temperature of the molten steel from dissipating; the second is to control and adjust the molten steel flow field in the crystallizer; the third is to avoid secondary oxidation of the molten steel.

[0003] The use of the submerged nozzle will directly affect whether the entire continuous casting process can proceed normally. In the early stage of steel casting, when the high-temperature molten steel flows through the submerged nozzle, a large thermal stress will be generated inside it, which may cause it to crack. The submerged nozzle body is subject to the thermal stress caused by the temperature difference between the inside and outside of the nozzle, the inner wall is strongly eroded by the high-temperature molten steel, and the external slag line is strongly eroded by the continuous casting protective slag. Therefore, the body of the submerged nozzle must have good thermal shock resistance and sufficient strength at room temperature and high temperature, the inner wall must have good resistance to erosion by high-temperature molten steel, and the slag line must have good resistance to erosion by protective slag.

[0004] Generally, for continuous casting submerged nozzle, the main body is made of Al2O3-C material with a C content ≥25%, the slag line is made of ZrO2-C material with a ZrO2 content of 73-78% and a C content of 12-16%, and the inner pore body (in contact with molten steel) is made of Al2O3-SiO2 material with an Al2O3 content of 65-80% and a SiO2 content of 15-30%.

[0005] At present, steel mills are trying their best to increase the number of continuous casting furnaces, which can not only reduce the cost of tundish refractory materials including the three major parts of continuous casting and tundish baking, but also increase the number of normal castings, reduce the number of non-steady-state castings, and improve the qualified rate of products. Gradually increasing the number of continuous casting furnaces is a requirement for the further development of continuous casting technology and quality in steel mills. The increase in the number of continuous casting furnaces puts higher requirements on the corrosion resistance of refractory materials in the tundish system, including the submerged nozzle. As the number of continuous casting furnaces increases, the slag line erosion of the submerged nozzle increases, and the residual thickness becomes thinner to a certain extent, the slag line will be perforated and the final casting will occur. Therefore, under the condition of using a high number of continuous casting furnaces, it is necessary to improve the corrosion resistance of the submerged nozzle, especially the corrosion resistance of the slag line against the protective slag.

[0006] The submerged nozzle includes an integral nozzle and a split nozzle. The integral nozzle has good integrity and is not easy to absorb air. The split nozzle can be quickly replaced in the middle of continuous casting with a high number of continuous casting furnaces. The existing submerged nozzle has poor corrosion resistance. The slag line position needs to be adjusted once when using 2-3 furnaces to meet the requirements of multi-furnace continuous casting. For the production of a high number of continuous casting furnaces, steel mills generally use quick-change nozzles to achieve it. However, for some high-quality steel grades, the quality requirements are high, and there is a risk of air absorption when using quick-change nozzles. Therefore, while the number of continuous casting furnaces increases, high-quality steel grades still hope to use an integral submerged nozzle to stabilize and improve the quality of molten steel. At this time, the insufficient corrosion resistance of the slag line of the submerged nozzle has become a limiting factor for the increase in the number of continuous casting furnaces. Generally, the corrosion resistance is improved by thickening the slag line position, but due to the limitation of the narrow width of the crystallizer, the thickening of the slag line is limited.

[0007] Chinese patent CN03119152.5 discloses "a highly corrosion-resistant aluminum-zirconium-carbon immersion nozzle". The aluminum-zirconium-carbon material of the immersion nozzle is composed of the following components by weight percentage: 9-20% flake graphite, 65-90% stabilized zirconium oxide, 0.5-5% boron nitride, and 0.5-5% metallic silicon powder. The immersion nozzle of this patent has high thermal shock stability, greatly improves the corrosion resistance of the slag line, and increases the service life. However, it is necessary to add very expensive boron nitride, which will significantly increase the manufacturing cost of the immersion nozzle.

[0008] Chinese patent CN200810230072.X discloses "a composition for making a submerged nozzle", the main composition is composed of the following raw materials by weight: 3-7 parts of feldspar, 50-70 parts of corundum, 3-7 parts of silicon carbide, 10-30 parts of graphite, and 5-15 parts of phenolic resin; the composition of the slag line is composed of the following raw materials by weight: 60-80 parts of zirconium oxide, 3-7 parts of zirconium boride, 10-20 parts of graphite, and 5-15 parts of phenolic resin. Zirconium boride is used to improve corrosion resistance, but since ZrB2 is expensive, it will significantly increase the manufacturing cost of the submerged nozzle.

[0009] Chinese patent CN201010236300.1 discloses "silicon-free submerged nozzle and its manufacturing method". The weight percentage of the main body material components is: flake graphite 15-35%, white corundum 35-55%, aluminum titanate 20-50%; the weight percentage of the slag line material components is: flake graphite 15-25%, zirconium oxide 40-75%, aluminum titanate 0-40%. Under the condition of not affecting the product's thermal shock resistance, corrosion resistance, scouring resistance and long service life, the nozzle blockage is effectively prevented to promote the continuous casting production and stable improvement of quality. Adding aluminum titanate can improve thermal shock resistance, but the zirconium oxide content is not increased, and the corrosion resistance of the slag line cannot be improved.

[0010] Chinese patent CN201210081010.3 discloses "an immersed nozzle and its preparation method". The raw materials and their contents in the slag line are: 70-90wt% of calcium oxide-partially stabilized zirconia, 3-8wt% of flake graphite, 0.5-5wt% of expanded graphite, 1-5wt% of SiC powder, 0.5-5wt% of elemental Si powder, 0.5-3wt% of B4C powder and 3-8wt% of thermosetting phenolic resin. Expanded graphite is used to replace part of the flake graphite. Expanded graphite can improve the thermal shock resistance of the material, but is not good for the material's oxidation resistance.

[0011] Chinese patent CN201210048696.6 discloses "non-oxide reinforced submerged nozzle slag line material". The composition of the slag line material is ZrB2: 5.5-8%, m-ZrO2: 75-80%, and graphite: 6-8%. However, ZrB2 is expensive, which will significantly increase the cost of the nozzle and cannot significantly improve the corrosion resistance of the slag line.

[0012] Existing continuous casting machine submerged nozzle slag line materials are mostly ZrO2-C. Since ZrO2 has poor thermal shock resistance, the slag line material must contain enough C to ensure thermal shock resistance requirements, otherwise it is easy to crack during use. However, it is necessary to add enough C content to meet the thermal shock resistance of the slag line. How to ensure that the slag line has good thermal shock resistance while further improving the erosion resistance of the slag line to meet the continuous casting process with an increasing number of continuous casting furnaces is a problem that needs to be solved now. Summary of the invention

[0013] The object of the present invention is to provide a continuous casting submerged nozzle slag line and an submerged nozzle, to ensure that the submerged nozzle slag line has a higher thermal shock resistance while further improving the corrosion resistance of the slag line, thereby increasing the number of continuous casting furnaces, which is beneficial to improving the quality of the ingot and ensuring the smooth continuous casting production of products with high continuous casting furnace number requirements; and, by improving the corrosion resistance of the inner pore body material to improve the inner pore body, the slag line perforation caused by a high casting furnace number can be avoided to a certain extent, thereby greatly enhancing the safety of the submerged nozzle.

[0014] In order to achieve the above object, the present invention provides the following technical solutions:

[0015] A continuous casting submerged nozzle slag line, the components of which are as follows by weight: stabilized zirconia + monoclinic zirconia ≥ 85%, nano carbon black 0.5-3.0%, flake graphite 3-9%, phenolic resin 2-7%, and at the same time ensure: 0 < monoclinic zirconia ≤ 5%.

[0016] The erosion rate of the slag line of the present invention is 0.029-0.036 mm / min.

[0017] The present invention also provides an immersed nozzle prepared using the above slag line, which includes a nozzle body, a slag line and an inner pore body, wherein the inner pore body material includes, by weight percentage: spinel: 60-80%, corundum: 15-30%, and C: 3-4%.

[0018] Preferably, the nozzle body is Al2O3-C.

[0019] In the continuous casting submerged nozzle slag line of the present invention:

[0020] Zirconia is added in combination of stable zirconia and monoclinic zirconia, in which the added monoclinic zirconia is unstable zirconia. When a small amount of monoclinic zirconia is added, as the temperature rises, the monoclinic zirconia transforms into tetragonal zirconia, which will cause volume shrinkage and produce microcracks in the material. The existence of microcracks can absorb thermal stress, achieve phase change toughening, and improve the thermal shock resistance of the material. It is necessary to ensure that the weight percentage of the added monoclinic zirconia is not more than 5%. If it is more than 5%, the crystal transformation of the monoclinic zirconia will produce more cracks, which will affect the strength of the material. At the same time, the slag will penetrate from the cracks, thereby affecting the material's corrosion resistance.

[0021] At the same time, the carbon added to the slag line material of the present invention adopts flake graphite and nano carbon black. The nano carbon black has high purity, small particle size (particle size is 20-60nm) and uniformity, and is easy to disperse and mix. The nano carbon black has a small particle size and is easy to fill in the cracks generated by monoclinic zirconia to form a nano carbon network. On the one hand, it is beneficial to absorb the thermal stress generated during the expansion and contraction process and improve the thermal shock resistance; on the other hand, it prevents the slag from penetrating into the interior of the zirconia material from the cracks, avoiding the erosion of the material by the slag, thereby improving the corrosion resistance of the slag line. The addition amount of nano carbon black is controlled at 0.5-3%. If the weight percentage is less than 0.5%, the effect of improving the thermal shock resistance is small. If the weight percentage is greater than 3%, the strength of the material will be reduced.

[0022] The present invention avoids the decrease in thermal shock resistance of the slag line due to the reduction of carbon content in the zirconium-carbon material by jointly adding monoclinic zirconium oxide and nano carbon black, and can maintain the thermal shock resistance of the slag line at a high level under the condition of less carbon content.

[0023] The present invention can increase the ZrO2 content in the slag line to more than 85% by reducing the carbon content in the slag line material, and further improve the corrosion resistance of the slag line material under the premise of ensuring that the slag line has high thermal shock resistance.

[0024] Furthermore, the submerged nozzle prepared by the slag line of the present invention is improved in the material of the inner pore body. The inner pore body material is mainly spinel, with a small amount of corundum added, and the carbon therein is the residual carbon of the binder resin. The improvement of the corrosion resistance of the inner pore body improves the overall corrosion resistance of the submerged nozzle. When the slag line is thinly corroded, the inner side of the slag line is supported by the inner pore body with good corrosion resistance, which reduces the risk of slag line perforation, thereby greatly enhancing the safety of the submerged nozzle. The existing submerged nozzle inner pore body is Al2O3-SiO2-C material, which contains 15-30% SiO2, and its corrosion resistance is affected.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] The present invention changes the crystal structure of ZrO2 and C added to the slag line, and through the composite effect of nano carbon black and monoclinic zirconia, more carbon is filled into the zirconia, which is beneficial to absorb the thermal stress generated during the expansion and contraction process, thereby ensuring that good thermal shock resistance can be achieved even when a small amount of C is added to the slag line. On the basis of ensuring the thermal shock resistance of the slag line, the total ZrO2 content can be increased to more than 85%, further improving the corrosion resistance of the slag line, thereby increasing the number of continuous casting furnaces. The increase in the number of continuous casting furnaces not only reduces the cost of the continuous casting process, but also helps to improve the quality of the ingot.

[0027] Furthermore, the present invention improves the corrosion resistance of the inner pore body by improving the material of the inner pore body. When the slag line is corroded to a relatively thin layer, the inner side of the slag line is supported by the inner pore body with good corrosion resistance, thereby reducing the risk of slag line perforation, thereby greatly enhancing the safety of the submerged nozzle.

[0028] The raw material components used in the slag line of the present invention are only ZrO2 and C, and there is no need to add expensive raw materials such as boron nitride and zirconium boride, so the cost is low and meets the requirements of large-scale production. DETAILED DESCRIPTION

[0029] The present invention is further described below in conjunction with specific embodiments.

[0030] The materials used for the slag lines of the embodiments of the present invention and the comparative examples are shown in Table 1.

[0031] The submerged nozzle is prepared by using the existing submerged nozzle production process, adopting the slag line composition, Al2O3-C for the nozzle body, and spinel and corundum for the inner pore body.

[0032] The erosion performance test adopts the crucible anti-slag method:

[0033] A crucible sample with a crucible hole of Φ25×25 was used. Protective slag was placed in the crucible hole and calcined at 1560°C for 3 hours. After cooling, the crucible was cut open and the erosion depth was measured. The calculated erosion rate is shown in Table 2.

[0034] Thermal shock resistance test:

[0035] According to the national standard GB / T 30873-2014, the sample is heated to 1100℃ in the furnace, kept warm for 15min, water-cooled for 3min, air-cooled for 5min, and then put into the furnace again. This process is repeated 5 times to measure the residual strength retention rate of the slag line material. The higher the residual strength retention rate, the better the thermal shock resistance. For specific performance, see Table 2.

[0036] It can be seen from Table 2 that the erosion rate of the slag line of the present invention is 0.029-0.036 mm / min, which is 37.9-44.8% higher than that of the slag line in the comparative example.

[0037] The residual strength of the embodiment of the present invention and the comparative example is very close, indicating that the thermal shock resistance of the slag line of the embodiment of the present invention and the comparative example is equivalent, which indicates that the present invention further improves the anti-corrosion performance of the slag line on the basis of ensuring that the slag line has good thermal shock resistance.

[0038] Table 1 Unit: Weight percentage

[0039] <![CDATA[Stable ZrO2]]> <![CDATA[Monoclinic ZrO2]]> Flake Graphite Nano Carbon Black Phenolic resin Example 1 80.4 5 7.3 0.7 6.6 Example 2 83.3 4 7.0 1.2 4.5 Example 3 83 2 6.8 1.8 6.4 Example 4 83.8 3 4.5 2.4 6.3 Example 5 85 3 4.0 2.8 5.2 Example 6 88 5 3.8 1.2 2.0 Example 7 86.5 5 2.3 3.0 3.2 Comparative Example 1 75 ― 16.5 ― 8.5 Comparative Example 2 78 ― 14.5 ― 7.5 Comparative Example 3 81 ― 12 ― 7.0

[0040] Table 2

[0041]

[0042]

Claims

1. A continuous casting submerged nozzle slag line, the components of which are as follows by weight: stabilized zirconia + monoclinic zirconia ≥ 85%, nano carbon black 0.5-3.0%, flake graphite 3-9%, phenolic resin 2-7%, and at the same time ensure: 0 < monoclinic zirconia ≤ 5%.

2. The submerged nozzle slag line according to claim 1, characterized in that: The erosion rate of the slag line is 0.029-0.036 mm / min.

3. An immersion nozzle prepared by using the slag line according to claim 1 or 2, characterized in that: It comprises a nozzle body, a slag line and an inner pore body; the weight percentage of the components of the inner pore body is: spinel: 60-80%, corundum: 15-30%, C: 3-4%.

4. The submerged nozzle according to claim 3, characterized in that: The nozzle body is Al2O3-C.

Citation Information

Patent Citations

  • Low-carbon inner hole body-contained submersed nozzle

    CN105983684A

  • Composite long runner gate for continuous casting

    CN2327474Y